"Pupus Putus Sekolah" Digital Comic as a Medium for Reflecting the Reality of School Dropouts in Indonesia - Achmad Nur Kholis; Rizka Kurnia Mailinda (TAMA: Journal of Visual Arts, 2026)
School dropout issues in Indonesia through the digital comic Pupus Putus Sekolah by Kurnia Harta Winata, while evaluating its effectiveness as a medium for social advocacy. Education in Indonesia faces a significant challenge with high dropout rates, particularly at the high school level which reaches 21.61% due to economic, access, and social factors. This research employs a qualitative descriptive method with a content analysis approach, utilizing Djelantik’s Aesthetic Theory (form, weight, and appearance) and Social Psychology to examine visual and narrative elements. The findings reveal that Pupus Putus Sekolah effectively mirrors the complex reality of underprivileged children through its protagonist, Pupus. Visually, the comic utilizes a cartoon-style illustration and a warm, neutral color palette to build emotional closeness and simplify serious social themes for a broader audience. Narratively, the story highlights that dropping out of school is not merely an economic issue but is also tied to psychological burdens and a formal education system that sometimes fails to accommodate children’s diverse needs. The "apprentice" learning model introduced in the plot offers a reflective alternative to non-formal education. The study concludes that digital comics are a powerful tool for social campaigns; their vertical layout on platforms like Webtoon and their ability to foster empathy through storytelling make them more engaging than traditional media. Reader engagement and moral integration within the dialogue further prove that Pupus Putus Sekolah serves as both a reflective educational medium and a strategic instrument for raising social awareness. Keywords: Pupus Putus Sekolah, comic, Webtoon, school dropout, social campaign.